Architecture at the End of the Earth: Photographing the Russian North - Kathleen Duff (2017)
Review of Architecture at the End of the Earth: Photographing the Russian North, Reviewed January 2017 by Kathleen Duff, Visiting Researcher, Harvard College Library, artandarchitecturekmd@gmail.com.